SOCIALCONSTRUCTION OF CORRUPTIONINNIGERIA (2023)
Globally, corruption threatens good governance, service delivery and the rule of law. In Nigeria, it undermines efficiency in organisations and institutions. Existing studies on corruption examined causes, measurement, consequences, prevalence and strategies for fighting corruption. However, scant attention has been paid to the social construction of corruption. This study was, therefore, designed to identify behaviours defined as corrupt activities; predisposing factors; strategies used to execute corrupt practices; factors that determine people’s receptivity to corruption; the role of the media in its construction; and how power relations moderate corrupt practices in Abuja.The social construction theory provided the framework, while a cross-sectional design was employed. Abuja was purposively selected based on the high concentration of federal ministries, departments and agencies. Three Area Councils (Abuja Municipal, Bwari and Gwagwalada) were randomly selected. Using Yamane’s (1967) sample size determination formula, 1300 respondents were sampled. Systematic sampling was used to proportionately administer a structured questionnaire to respondents (aged ≥18 years) in Abuja Municipal (438), Bwari (433) and Gwagwalada (429) councils. Twenty-one key informant interviews were conducted with two judges, six lawyers, six civil society groups’ officials, and seven community leaders. Thirty in-depth interviews (six with each group) were conducted with lecturers, politicians, contractors, procurement officers and commercial drivers. Nine focus group discussion sessions (three in each) were held with students, journalists and anti-graft agencies’ officials to examine the social construction of corruption. Quantitative data were analysed using descriptive statistics and Chi-square at p≤0.05 while the qualitative data were content-analysed.The respondents’ ages were 34.87±10.82 years, with 47.8% working in the public sector. The majority of the respondents (92.2%) defined certain behaviour – nepotism, conversion of public property to private use, diversion of public funds to unbudgeted projects – as highly corrupt activities. This was significantly related to age (x2=47.12), education (x2=29.86), occupation (x2=65.11) and income (x2=34.82). Greed (66.4%), poverty (22.5%) and weak laws (11.1%) predisposed people to corrupt behaviour. Ineffective law enforcement (48.6%) and loopholes in government financial systems (14.9%) made public office holders vulnerable to corruption. Distortion of financial records (98.5%), payment of ghost workers (98.5%) and charging unauthorised fees (97.9%) were strategies reported to be used to execute corruption. Gift-giving culture (86.8%) and payment of fines in lieu of a jail term by corrupt officials (93.6%) strongly determined people’s receptivity to corruption. Trivialisation of corrupt cases and biased reportage by the media during trials, due to fear of persecution of reporters, affected how society constructed corruption. When seeking public service, the person with less power was more inclined to offer a bribe than the one in a position of authority.Greed, poverty and shabby implementation of anti-corruption laws predisposed people to corrupt behaviour and influenced how they construct corruption. There is a need for relevant authorities to sensitise the public against patronising the culture of corruption.